Effects of Methamphetamine on Testes Histopathology and Spermatogenesis Indices of Adult Male Rats - Arezoo Saberi; Gholamreza Sepehri; Zohreh Safi; Behzad Razavi; Faranak Jahandari; Kouros Divsalar; Ehsan Salarkia (Addiction and Health, 2017)
Background: Methamphetamine (mAMP) as a recreational drug has devastating effects on the central nervous system (CNS). Several studies have shown that mAMP has inhibitory effects on oogenesis and spermatogenesis, and causes impaired fertility. This study designed to investigate the effect of mAM Padministration on histological changes and spermatogenesis indices in the testis of adult male rats.Methods: In this experimental study, 50 male Wistar rats were randomly divided into control (received no treatment, n = 10), vehicle (received saline for 7 and 14 days, n = 20), and experimental group [received mAMP, 5 ml/kg, intraperitoneal (IP) for 7 and 14 days, n = 20]. Testicular tissue samples were stained by hematoxylin and eosin (H&E) technique. For histological study, we counted the number of spermatogonia, spermatocytes and Leydig cells. Spermatogenesis indices which include: tubular differentiation index (TDI), spermiogenesis index (SI), repopulation index (RI) and the mean seminiferous tubules diameter (MSTD) were studied. Data were analyzed by one-way ANOVA, using SPSS software. P < 0.05 was considered statistically significant.Findings: This study showed that mAMP caused a significant decrease in number of seminiferous tubules cells and spermatogenesis in treated group compared with the control group. Moreover, results showed a significant decrease in spermatogenesis indices including TDI, SI, RI, and MSTD in 14th day, compared to control group (P < 0.001).Conclusion: The data showed the adverse effects of mAMP administration (for 7 and 14 days) on testes structure and spermatogenesis indices in rat testis tissue. The underlying mechanism(s) needs further investigation.